National Security Surveillance in an Age of Terror: Statutory Powers & Charter Limits - Penney, Steven (2010)
The communications surveillance powers granted to Canada's national security agencies have rarely resulted in prosecution and, as a result, have been subject to very little judicial, academic, or public scrutiny. However, as the state increasingly seeks to prosecute alleged terrorists, courts will have to interpret the scope of these powers and decide whether they violate section 8 of the Canadian Charter of Rights and Freedoms (the Charter). A review of the powers granted to police, the Canadian Security Intelligence Service (CSIS), and the Communications Security Establishment Canada (CSEC) reveals two constitutional infirmities: allowing police to conduct communications surveillance in terrorism investigations without establishing investigative necessity, and allowing CSEC to intercept domestic communications without prior judicial authorization. Put simply, these powers should be found to violate section 8 of the Charter because they substantially infringe on the privacy of innocent Canadians, especially of Muslim or Arab background, while doing little to advance national security